2018
DOI: 10.1590/1980-57642018dn12-020014
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of the Brief Visuospatial Memory Test - Revised in Brazilian multiple sclerosis patients

Abstract: Cognitive Impairment (CI) is a common and distressing problem in Multiple Sclerosis (MS). Its identification is complicated and sometimes omitted in the routine evaluation by neurologists. The BICAMS (Brief International Cognitive Assessment for Multiple Sclerosis) is a promising tool to overcome this difficulty. However, there is some concern regarding the subjectivity in scoring of the BVMT-R (Brief Visuospatial Memory Test - Revised), one of its components.Objective:To evaluate the reliability of the BVMT-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…While BVMT examines visuospatial episodic memory, the encoding and immediate recall of episodic information is partially dependent on working memory [66]. In part due to this overlap in cognitive processes [67], the source of performance deficits on the CVLT immediate recall is suggested to be similar to that on the BVMT [51,68,69]. Coinciding evidence of similar activation patterns in brain regions, including the prefrontal cortex and hippocampus, when engaged in visuospatial and immediate recall tasks [70] further suggests some lack of specificity in the assessments.…”
Section: Discussionmentioning
confidence: 99%
“…While BVMT examines visuospatial episodic memory, the encoding and immediate recall of episodic information is partially dependent on working memory [66]. In part due to this overlap in cognitive processes [67], the source of performance deficits on the CVLT immediate recall is suggested to be similar to that on the BVMT [51,68,69]. Coinciding evidence of similar activation patterns in brain regions, including the prefrontal cortex and hippocampus, when engaged in visuospatial and immediate recall tasks [70] further suggests some lack of specificity in the assessments.…”
Section: Discussionmentioning
confidence: 99%
“…32 Meanwhile, our results revealed a significant correlation between BMVT and MSQOL-PH. BMVT is proven to be a reliable instrument to evaluate visuospatial learning in patients with MS. 42 Deficits of visuospatial learning and memory are common in patients with MS and correlate to atrophy in the hippocampus region. 43 We found that there was a statistically significant association between specific aspects of cognitive decline and QOL from the perspective of both mental and physical health.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Meanwhile, our results revealed a significant correlation between BMVT and MSQOL-PH. BMVT is proven to be a reliable instrument to evaluate visuospatial learning in patients with MS. 42 Deficits of visuospatial learning and memory are common in patients with MS and correlate to atrophy in the hippocampus region. 43 …”
Section: Discussionmentioning
confidence: 99%
“…There is an emerging interest on the study of cognitive dysfunction in Brazilian patients with MS [17][18][19][20] 21 . Conversely, Damasceno et al showed that patients with relapsing-remitting MS evolved with cognitive decline even if they had minimal or no evidence of disease activity 22,23 .…”
Section: Introductionmentioning
confidence: 99%